Image and Graphics : 8th International Conference, ICIG 2015, Tianjin, China, August 13-16, 2015, Proceedings, Part III - Zhang, Yu-Jin.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed conference proceedings of the 8th International Conference on Image and Graphics, ICIG 2015 held in Tianjin, China, in August 2015. The 164 revised full papers and 6 special issue papers were carefully reviewed and selected from 339 submissions. The papers focus on various advances of theory, techniques and algorithms in the fields of images and graphics.
3D Shapes Isometric Deformation Using In-tSNE -- 3D Visual Comfort Assessment via Sparse Coding -- A Combination Method of Edge Detection and SVM Filtering for License Plate Extraction -- A Comparative Study of Saliency Aggregation for Salient Object Detection -- A Digital Watermarking Algorithm for Trademarks Based on U System -- A Fast and Accurate Iris Segmentation Approach -- A Fast Edge Detection Model in Presence of Impulse Noise -- A Foreground Extraction Method by Using Multi-Resolution Edge Aggregation Algorithm -- A Generalized Additive Convolution Model for Efficient Deblurring of Camera Shaken Image -- A High Dynamic Range Microscopic Video System -- A Learning Classes-Based No-Reference Image Quality Assessment Algorithm Using Natural Scenes Statistics -- A Locality Preserving Approach for Kernel PCA -- A Method for Tracking Vehicles under Occlusion Problem -- A Method of Facial Animation Retargeting Based on Motion Capture -- A Modified Fourier Descriptor for Shape-Based Image Recognition -- A Multiple Image Group Adaptation Approach for Event Recognition in Consumer Videos -- A Multi-Scale SAR Scene Matching Algorithm Based on Compressed Contour Feature -- A New Approach for Orthogonal Representation of Lunar Contour Maps -- A New Method of Object Saliency Detection in Foggy Images -- A New Optimization Algorithm for HEVC -- A New Radiation Correction Method for Remote Sensing Images Based on Change Detection -- A New Supervised Manifold Learning Algorithm -- A Nonlocal Based Two-Step Method Applied to MRI Brain Image Segmentation -- A Non-Seed-Based Region Growing Algorithm for High Resolution Remote Sensing Image Segmentation -- A Novel Control Point Dispersion Method for Image Registration Robust to Local Distortion -- A Novel FOD Classification System Based on Visual Features -- A Novel Fusion Method of Infrared and Visible Images Based on Non-subsampled Contourlet Transform -- A Novel Improved Binarized Normed Gradients Based Objectness Measure through the Multi-Feature Learning -- A Novel Method 3D Gait Curve for Human Identification -- A Novel Method for Barcode Detection and Recognition in Complex Scenes -- A Novel Method for Predicting Facial Beauty under Unconstrained Condition -- A Novel NSCT Fusion Algorithm for Images Based on CS and DWNMF -- Novel Prediction Algorithm in Gaussian-Mixture Probability Hypothesis Density Filter for Target Tracking -- A Point in Non-Convex Polygon Location Problem Using the Polar Space Subdivision in E2 -- A Research of Forest Fire Detection Based on the Video Compression -- A Reversible Data Hiding Scheme Using Ordered Cluster-Based VQ Index Tables for Complex Images -- A Stroke Width Based Parameter-Free Document Binarization Method -- A Style Transformation Method for Printed Chinese Characters -- A Unified Fidelity Optimization Model for Global Color Transfer -- A Vision-Based Method for Parking Space Surveillance and Parking Lot Management -- A Well-behaved TV Logo Recognition Method Using Heuristic Optimality Checked Basis Pursuit Denoising -- An Automatic Landmark Localization Method for 2D and 3D Face -- An Improved Fiber Tracking Method for Crossing Fibers -- An Iterative Method for Gastroscopic Image Registration -- An Optimized Scheme to Generating Support Structure for 3D Printing -- An Outlier Removal Method by Statistically Analyzing Hypotheses for Geometric Model Fitting -- Photon Shooting with Programmable Scalar Contribution Function -- Real-Time locating Method for Palmvein Image Acquisition -- Real-Time Panoramic Image Mosaic via Harris Corner Detection on FPGA -- Real-Time Robust Video Stabilization Based on Empirical Mode Decomposition and Multiple Evaluation Criteria -- Real-time Underwater Image Contrast Enhancement through Guided Filtering -- Recent Progress of Structural Variations Detection Algorithms Based on Next-Generation Sequencing: A Survey -- Recognition of in-Air Handwritten Chinese Character Based on Leap Motion Controller -- Robust and Real Time Lane Marking Detection for Embedded System -- Robust Contour Tracking via Constrained Separate Tracking of Location and Shape -- Robust Face Hallucination via Similarity Selection and Representation -- Single Remote Sensing Image Haze Removal Based on Spatial and Spectral Self-adaptive Model -- Small Infrared Target Detection Based on Low-Rank Representation -- Sophisticated Tracking Framework with Combined Detector -- The Research of Long Time Occlusion Problem Based on Object Permanence -- The Segmentation Interventricular Septum from MR Images -- Two-Stage Learning to Robust Visual Track via CNNs -- Undersampled Dynamic MRI Reconstruction by Double Sparse Spatiotemporal Dictionary -- Underwater Image Devignetting and Colour Correction -- Video Based Face Tracking and Animation -- Video Stabilization via Piecewise Linear L1 Optimization for Airship Earth Observation.
Keywords: Computer science; Computer Science, general